Stroking parameters patterns in a training set performed at the critical velocity - Campos, A.; Figueiredo, P.; Vilas-Boas, J. P.; Fernandes, R. J. (The Open Sports Sciences Journal, 2010)
Swimming critical velocity is defined as the maximum velocity that could be maintained during a long period of time without exhaustion, being accepted as a valid parameter to assess aerobic capacity. Our purpose was to observe the patterns of the stroking parameters during a typical aerobic capacity training set conducted at critical velocity Thirty six juvenile swimmers performed front crawl 200 and 800 m tests at maximum intensity. Critical velocity and critical stroke rate were assessed as the slope of the regression line obtained between the test distances, and between the total number of stroke cycles in each test distance, and the respective times, respectively. Twenty-four hours after, swimmers performed a typical aerobic capacity training set (8x200 m front crawl, 20s rest). It were observed moderate to high correlation coefficients between critical velocity values and mean velocity of the aerobic training set (r=0.84 and r=0.66, respectively for female and male groups). The same phenomenon was observed when considering the relationship between critical stroke rate and the mean stroke rate obtained in the training set (r=0.93 for both gender groups). Velocity decreased from the 1st to 2nd repetitions, becoming stable in the middle of the set and increasing during the last repetition. Stroke rate was stable during the first seven repetitions and increased from the 7th to the 8th repetition. Stroke length was stable in the female group and, in the male group, increased from the 2nd to the 3rd repetition, followed by a decrease in the final of the training set.